Environmental Influences on Frozen Epididymal Sperm Cell Viability in White-Tailed Deer - Muñoz-Hernandez, Nadia Carolina; Lagunes-Moreno, Claudia Karina; Barrientos-Villeda, Manuel; Lammoglia-Villagomez, Miguel Angel; Avalos-Rosario, Ivan I.; Valverde, Anthony; Barrientos-Morales, Manuel (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The objective of this study was to evaluate the association between Temperature and Humidity Index (THI), age, and post-collection time with post-thawing sperm cell parameters such as progressive motility, viability, morphology, and cytoplasmic droplets. Samples were collected from 4 male white-tailed deer after regulated hunting. THI was calculated on collection days. Two THI categories were determined, ≥70 and <70. Thawed semen was placed on a slide and observed under a phase-contrast microscope to evaluate the progressively motile sperm cells. Morphology, viability, and cytoplasmic droplets were assessed on a smear stained with eosin-nigrosine and classified as normal or abnormal, viable or not viable, and present or absent, respectively. When THI was ≥70, the progressive motility (51.0 vs 30.67%), sperm viability (51.0 vs 36.33%), and the proportion of sperm cells with normal morphology (65.0 vs 37.67%) were higher than to days with a THI <70, without differences in the presence of cytoplasmic droplets. The 4-years bucks had a higher proportion of sperm cells with normal morphology (81.0 vs 35.5 and 26.0%) and cytoplasmic droplets (27.0 vs. 12.0 and 7.5%) compared to 2- and 3-year-old animals. Samples processed after 4 hours (51.0%) had a higher progressive motility than samples processed after 6 and 8 hours (32.0 and 25.0%, respectively). Spermatozoa processed after 8 hours (30.0%) had a lower viability than spermatozoa processed after 4 hours (51.0%). Compared to samples processed after 6 and 8 hours, those processed after 2 and 4 hours had a higher proportion of sperm cells with normal morphology (26.0 and 6.0 vs 81.0 and 65.0%, respectively). Samples processed after 2 hours had a higher (27.0 vs. 12.0%) proportion of sperm cells with cytoplasmic droplets than to those processed after 6 hours. High THI favors progressive motility and sperm viability. The older bucks had a greater proportion of sperm cells with normal morphology and cytoplasmic droplets than to the young ones. The greater progressive motility, viability, morphology, and presence of cytoplasmic droplets were found when the samples were processed within the first 4 hours.